Case Report: Multimodal Imaging in a Rare Case of Morning Glory Disc Anomaly Complicated With Choroidal Ossification - Wang, Shuya; Wang, Xingrong; Wang, Ying; Bi, Hongsheng (Frontiers in Medicine, 2022)
Purpose The authors described a 7-year-old boy who was diagnosed with morning glory disc (MGD) anomaly in the right eye via fundus examination. However, during the head CT examination, a hyperdense choroidal lesion was discovered around the optic disc. Comprehensive investigations revealed that the lesion's characteristics were extremely consistent with choroidal osteoma (CO), so the patient was diagnosed with MGD with CO on his second visit. However, in the subsequent follow-up, the author discovered pigmentary alterations in the retinal pigment epithelium (RPE) in the patient's right eye. Finally, the diagnosis was corrected to MGD with choroidal ossification following a thorough etiological analysis. Meanwhile, the characteristics of choroidal ossification were described in detail through multimodal imaging in this article. Methods Retrospective review of a case note. Conclusions Similar to CO, choroidal ossification is the consequence of structured osseous tissue formation regulated by osteoblasts and osteoclasts. It consists of bone trabecular and vascular components and is difficult to be distinguished from CO on imaging examinations. In contrast to the congenital prevalence of CO, there are often incentives for the occurrence of choroidal ossification. These inducements will eventually mediate the inflammation in the eye, resulting in the activation of many cytokines and the production of choroidal ossification. Around one-third of patients with MGD will experience retinal detachment, and in certain cases, the subretinal fluid will be absorbed spontaneously, resulting in alterations to the RPE. These processes can activate inflammatory factors in the eye, bringing about a cascade of abnormalities, including the development of CO. Therefore, the proper diagnosis of disease should not be made exclusively on the basis of the imaging findings. A thorough analysis of the epidemiology and etiology is crucial.